The Impact of Implementing Green Economy on Company Profits in the Long Term at Pt Ace Hardware Indonesia Tbk. - Nia Anisyah; Puan Mayzara; Veronica Erva; Maria Yovita R. Pardin (International Journal of Educational and Life Sciences, 2024)
This study analyzes the relationship between the application of green economy concepts, financial performance, and employee responses to sustainability issues at PT Ace Hardware Indonesia Tbk. Through data analysis from financial reports, profit and loss reports, cash flow reports, as well as employee survey results, the findings show that there is a significant link between sustainable business practices and positive employee responses to sustainability issues. Moreover, economic equality reaching 48% among employees reflects the company's commitment to social inclusivity and equality in the workplace. From this analysis, it appears that the application of the green economy concept has the potential to increase company profitability and competitiveness in the long term. Based on these findings, several suggestions are provided to optimize the implementation of the green economy concept, including increasing employee awareness, developing broader environmental policies, and investing in green technology. Implementation of these suggestions is expected to strengthen PT Ace Hardware Indonesia Tbk's position as a sustainable company and increase its profitability, while also having a positive impact on the environment and society as a whole.